Análises proteômicas, anti-venômicas e isolamento de novas proteínas com atividade citotóxicas de venenos elapídicos - Paula Henriques Cruz Ciscotto (2011)
Coral snakes from Micrurus genus are the main representatives of the Elapidae family in South America. However, biochemical and pharmacological features of the constituents of their venoms remain poorly investigated. In this study, venomic analyses were carried out aiming a deeper understanding of the composition of the venoms of M. frontalis, M. ibiboboca, and M. lemniscatus. To achieve this goal, two-dimensional chromatography and mass spectrometry analyses, together with N-terminal sequencing were employed. In these three observed venoms, proteins with masses ranging from 6 to 8 kDa and 12 to 14 kDa, related to 3FTx and PLA2 protein families, respectively, were found to be the most abundant. We also report, for the first time, the N-terminal sequence of four new proteins purified from the M. lemniscatus venom that are similar to 3FTx, PLA2 and Kunitz-type protease inhibitor from other Micrurus and elapid venoms. Moreover, cross-reactivity among different Micrurus venoms and antivenoms (anti-M. corallinus, anti-M. frontalis, anti-M. ibiboboca and anti-Elapidic) was carried out by means of 2D-electrophoresis and immunoblotting assays. The generic anti-Elapid venom displayed the highest degree of cross-reactivity. Conversely, anti-M. corallinus reacted weakly against M. frontalis, M. lemniscatus, M. ibiboboca and M. spixii venoms. In gel digestions, followed by mass spectrometry analyses and databank similarity searching, revealed the most immunogenic protein families as similar to short and long neurotoxins, weak neurotoxins, PLA2, -bungarotoxin, venom protein E2, frontoxin III, L-amino acid oxidase and C-type lectin. The implications of our results for the production of Micrurus antivenoms are discussed. Additionaly, two proteins from 3FTx family, with molecular masses of 6435,4 Da and 6504,6 Da, were purified from the venom of M. Lemniscatus. Their toxicity against Leishmania and mammals cells was tested. Both proteins were toxic to promastigotic forms of the L. (L). amazonensis, leading to 49% and 39%, respectively, of death on the protozoan population in the 50 µg/mL concentration. However, both proteins were also toxic to mice macrophages.